“Evaluación de complejos micorrízicos asociados al cultivo de plántulas de cacao (Theobroma cacao)”. - Dorado Gutiérrez, Evelin Beatriz (2019)
SUMMARY Cocoa (Theobroma cacao L.) is one of the oldest and most important crops in the world, being the crop that sustains the economy of many countries in the world. In Ecuador, 350,000 ha are cultivated annually, mainly in the provinces of Guayas (Naranjal, Balao and Tenguel), the province of Los Ríos (Vinces, Babahoyo, Palenque Baba, Pueblo Viejo, Catarama and Ventanas) and in the province of Oro (Machala and Santa Rosa), with an average national yield of 0,4 tons / ha of dry cocoa. The objective of the research was to evaluate the mycorrhizal complexes associated with the cultivation of cocoa. The present investigation was carried out in the "La Victoria" farm belonging to Mr. Elio Gutiérrez Domínguez, located at Km 17 ½ of Vía Babahoyo - San Juan. We investigated 5 treatments with 4 repetitions, distributed in a completely randomized block design. For the evaluation of means, the Tukey test at 5% significance was used. At 30, 60 and 90 days the plant height, stem diameter, leaf length, leaf emission, leaf area were evaluated. After 120 days, root length was evaluated, radical biomass. Analyzes were carried out to determine the percentage of colonization and spore counts. The results determined that the application of Ecofungi in a dose of 3 g of substrate / plant, increased the growth with increments of 35 - 45 % in relation to the other treatments. The application of Ecofungi substantially influenced the growth and development of cocoa seedlings in the nursery. Larger stem diameter was obtained by applying Ecofungi on the treated plants. Larger leaf area was found with the application of the Ecofungi and Mycobacter strains. The root length was greater with the application of the Faciag strain. The radical biomass was greater by applying the Faciag and Ecofungi mycorrhizal strains to the seedlings. Greater percentage of colonization was achieved with Faciag and Ecofungi strains. The largest population of spores was found applying the Ecofungi strain. The correlation showed a very high value between root length and percentage of colonization. Keyword: mycorrhizae, seedlings, cocoa, nursery, spores.